Penggunaan Media Teknologi Digital Prezi sebagai Bahan Ajar Bahasa Indonesia dengan Tema Teks Biografi di Kelas X MAN 2 Kepahiang untuk Meningkatkan Pembelajaran Bahasa Indonesia - Melianda, Oki; Rustinar, Eli; Asmara , Adi (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This study is motivated by the low ability of students to explain the learning processes they undergo. During lessons, students often feel bored due to the use of only printed textbooks and blackboards, which results in a lack of understanding of the material presented by the educator. This research employs a qualitative descriptive method with the objective of evaluating the use of the digital media prezi as a teaching material for Indonesian language with a biographical text theme in grade X at MAN 2 Kepahiang. The findings indicate that the use of prezi digital media is highly effective in enhancing Indonesian language learning, making the material more engaging and comprehensible for students.